IMPLEMENTASI E-LEARNING MASA COVID-19 MATA PELAJARAN GEOGRAFI DI KELAS X SMAN 1 SUNGAI RAYA - Kristina Moni Agati; Sri Buwono; Putri Tipa Anasi (Universitas Tanjungpura, 2021)
AbstractThis research aims to know the implementation of E-learning based learning that have replaced the face-to-face learning method toward the tenth grader students of IPS at SMAN 1 Sungai Raya in Geography subject during Covid-19 pandemic. The type of the research had been used is descriptive with qualitative method with case study form research. The procedures of data collecting in this research are interviews, questionnaires and documentation. The result of research reveals that the implementation of learning by E-learning in the Geography subject learning process during Covid-19 pandemic for the tenth grader students of IPS at SMAN 1 Sungai Raya is synchronous due to simultaneously learning (Real Time). The assignments that had been given by the teacher not Real Time or carried out delay basis so means that asynchronous. The was synchronous because after the students had sent the assignment on Google Classroom, they directly saw their score in Real time or simultaneously. The suitability to basic competence and the achievement of the basic competence’s indicator for chapter I is about the Basic Knowledge of Geography and chapter II is about the Basic Mapping Knowledge, the students are understand enough about those material.Keywords:Geography Learning, Implementation E-learning, and Pandemic Covid-19